2021
DOI: 10.5005/jp-journals-10071-23594
|View full text |Cite
|
Sign up to set email alerts
|

Airway Resistance and Respiratory Compliance in Children with Acute Viral Bronchiolitis Requiring Mechanical Ventilation Support

Abstract: A bstract Background Acute viral bronchiolitis (AVB) is a very frequent disease that affects the lower airways of young children increasing the inspiratory and expiratory resistance in variable degree as well as reducing the pulmonary compliance. It would be desirable to know whether these variables are associated with the outcome. Objectives To evaluate the respiratory mechanics in infants with AVB requiring mechanical ventilation (MV) suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Second, PCV in comparison to VCV, underestimated the viscoelastic resistive component (P1–P PLAT ) by an average of 1.5 cm H 2 O. Third, contrary to other reports (9, 18), we found that the resistive (PIP–P1) and threshold (iPEEP) frictional components were negligible regardless of MV mode, even though most patients had critical bronchiolitis (19). Last, the peak inspiratory flow in decelerating flow was higher than squared-shaped flow, despite V t and Ti were kept the same.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, PCV in comparison to VCV, underestimated the viscoelastic resistive component (P1–P PLAT ) by an average of 1.5 cm H 2 O. Third, contrary to other reports (9, 18), we found that the resistive (PIP–P1) and threshold (iPEEP) frictional components were negligible regardless of MV mode, even though most patients had critical bronchiolitis (19). Last, the peak inspiratory flow in decelerating flow was higher than squared-shaped flow, despite V t and Ti were kept the same.…”
Section: Discussioncontrasting
confidence: 99%
“…We and others have reported pulmonary mechanics (i.e., inspiratory resistance [Rinsp], expiratory resistance [Rexp], static lung compliance, and dynamic lung compliance) pediatric patients undergoing invasive MV (7)(8)(9). Now, in our current study, we describe values of pulmonary resistance in pediatric patients undergoing invasive MV, adjusted for age and weight.…”
mentioning
confidence: 81%
“…All parents/family provided informed consent. Some of this research has been published previously (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The upper quartile of the measured inspiratory resistance in ventilated infants with bronchiolitis at a median age of 2.8 months has been reported at 176-186 cm H 2 O/L/s. 7 The percentage of change in the PTIdi after the application of the resistance was calculated as the difference in the PTIdi divided by the PTIdi before the application of the resistance times 100. During the measurements, the participants were closely monitored for chest wall distortion and oxygen desaturation.…”
Section: Application Of An External Inspiratory Flow Resistancementioning
confidence: 99%